Herbal Package to Reduce Pain of Uterine Contractions (Senggugut Pain) on Postpartum Mother - Erika; Agrina; Hasneli, Yesi (International Journal of Psychosocial Rehabilitation, 2020)
Childbirth is a long and tiring process and can even take a mother’s life. According to WHO (2018), as many as 303,000 women per year have lost their lives during childbirth as a result of complications arising from pregnancy. This is equivalent to around 830 women dying every day or one person every two minutes. The birth process causes pain in the birth canal. Pain is also experienced by the mother as a result of contractions due to changes in the uterine muscles becoming normal. The purpose of this study is to make a package of herbal ingredients that are useful for overcoming the pain of maternal uterine contractions or usually called as postpartum pain. Research methods. The method used in this study was the manufacture of herbal packages and then tested on 30 respondents of mothers after giving birth to the second child and so on who experience uterine contractions pain. Results. From the results of the study it was found that compressing the herbal package can reduce the pain of uterine contractions (senggugut pain) of mothers after giving birth. This means that mothers who are given herbal pack compresses have decreased postpartum pain. Recommendation. It is expected that this herbal concoction package will be able to help postpartum mothers increase their comfort, since this package is useful for reducing or managing pain due to uterine contractions after giving birth.